Effect of pressure and polishing technique on surface roughness of cold cured acrylic resin - Sianiwati Goenharto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
The smoothness of acrylic surface plays an important role in producing removable orthodontic appliances. Int this study, we examine the effect of pressure and polishing technique on surface roughness of cold cured acrylic resin. Forty eight samples were prepared and classified into two groups: acrylic resin polymerization with and without pressure. Each group was classified into four subgroups: being polished with abrasive stone, bur for acrylic, silicone polisher and without being polished as control group. Surface roughness was measured using surface roughness tester. The surface roughness of polymerized acrylic with and without pressure and polished with different technique was analyzed using One-Way ANOVA, continued by Dunnet test. T-test was done to know whether there was the effect of pressure on surface roughness after being polished using certain technique. The result showed that pressure and polishing technique affected surface roughness significantly (p = 0.001). On the group of polymerization with pressure, surface roughness resulted from polishing with bur of acrylic showed significant difference with silicone polisher, whereas on the group without pressure, polishing with bur of acrylic showed significant difference with abrasive stone. Of the three polishing techniques, there was significant difference of surface roughness of cold cured acrylic resin (t = 0.002). It is concluded that pressure and polishing technique affected the surface roughness of cold cured acrylic resin. Polishing technique using bur of acrylic, followed by abrasive paper, rotating felt cone and soft brush showed less surface roughness on the group of polymerization with or without pressure.